Exploring criminal justice - Regoli, Robert M. (Jones and Bartlett, 2008)
Crime and criminal justice today -- Criminal law : the foundation of criminal justice -- Crime, offenders, and victims -- Crime theory and social policy -- Policing history and systems -- Police organization and functions -- Police and the law -- Critical issues in policing -- The criminal courts : history and structure -- Prosecuting the accused : from initial appearance to plea bargain -- The trial -- Sentencing -- Corrections : history and structure -- Prisons -- Corrections in the community -- The juvenile justice system -- Terrorism and cyber crime